(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid integration of artificial intelligence into organizational processes has significantly transformed the way leaders make decisions, communicate, learn, and manage people. While AI increasingly supports analytical thinking, information processing, and operational efficiency, it cannot replace the distinctly human capacities that define sustainable leadership, including emotional maturity, ethical judgment, empathy, and the ability to build trust. These competencies remain fundamental for effective leadership in environments characterized by uncertainty, technological acceleration, and continuous organizational change. This paper examines the evolving relationship between artificial intelligence and emotional maturity within contemporary corporate mentoring. Rather than viewing AI as a substitute for human leadership, the article proposes a synergistic perspective in which technology enhances cognitive capabilities while emotionally mature leaders provide contextual understanding, ethical reflection, and meaningful interpersonal relationships. The paper argues that the future of leadership development depends on integrating technological intelligence with psychological competence rather than prioritizing one over the other. Drawing upon contemporary leadership research, organizational psychology, executive coaching, and emerging studies on artificial intelligence in management, this conceptual paper introduces a human-centered approach to corporate mentoring. It explores how emotionally mature leaders can effectively collaborate with AI systems while maintaining authentic communication, psychological safety, adaptive decision-making, and organizational trust.The article concludes that artificial intelligence should be regarded as an instrument that expands managerial capacity rather than replaces human leadership. Organizations that intentionally combine technological innovation with the development of emotional maturity are likely to cultivate more adaptive, resilient, and ethically responsible leaders capable of navigating the increasing complexity of modern organizational environments.